Application of STIFIn-Based Intelligence Concept on Students' Qur'an Memorization Achievement - Diana Kholidah; Asriana Kibtiyah; Khoirotul Idawati; Hanifudin Hanifudin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study discusses the Application of the STIFin-based intelligence Concept to Students' Al-Qur'an Memorization Achievements at MTs Madrasatul Qur'an Tebuireng Jombang. This study aims to investigate applying the Sensing, Thinking, Intuiting, Feeling, and Instinct (STIFIn)-based intelligence concept to students' Al-Qur'an memorization achievements at MTs Madrastul Qur'an Tebuireng Jombang. This study focuses on the analysis of the application of the STIFIn Intelligence concept in the achievement of memorizing the Al-Qur'an, student learning motivation and student learning styles in memorizing the Al-Qur'an, and Identification of supporting and inhibiting factors in the application of the STIFIn concept to students' Al-Qur'an memorization achievements at MTs Madrasatul Qur'an Tebuireng. The author uses a qualitative phenomenological approach. With domain data analysis: Taxonomic Analysis and Componential Analysis. The results of this study: Memorization achievement with the STIFIn approach will improve the quality of learning in students who already have a good basic fashohah. Facilitate accompanying teachers in motivating memorization of the Qur'an. Facilitate accompanying teachers and students in understanding the uniqueness of each student's learning style based on the dominant Intelligence Machine (MK) they have Learning style. Among the inhibiting factors found the intention/commitment is less istiqomah. On the other hand, strong support from the head of the madrasah serves as a key facilitating factor.